STRATEGI KREATIF DIGITAL STRATEGIS DALAM MENGELOLA TIKTOK ASTRA DIGITAL - Fauzul, Adhim (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study aims to analyze the application of creative digital strategies in managing TikTok content by Astra Digital. As a rapidly growing social media platform, TikTok requires a creative approach to enhance engagement and brand awareness. This research uses a qualitative method with data collection through direct observation, interviews, and literature studies related to digital marketing strategies and content management. The results show that Astra Digital applies a creative strategy based on data analysis and audience understanding, along with the use of multimedia features on TikTok such as filters and effects to enhance content appeal. Furthermore, the implemented strategy has proven effective in achieving business and marketing communication goals, increasing interaction between the company and its audience. The study also finds that the appropriate application of creative digital strategies can strengthen brand positioning in the market and boost user engagement. Regular evaluations and measuring campaign success with the right metrics also play a crucial role in improving the effectiveness of the applied strategy.Keywords: Brand Awareness, Creative Digital Strategy, Digital Marketing, Engagement, Tiktok